Maguti Tradition: Constructing the Mindset of Ngawi People a Symbolism Approach - Kodrat Eko Putro Setiawan; Devi Cintia Kasimbara; Estuning Dewi Hapsari; Wahyuningsih Wahyuningsih (Indonesian Journal of Social Science Education (IJSSE), 2024)
Maguti is one of the traditions that still exist in Jagir Village, Sine Subdistrict, Ngawi Regency, East Java. This research aims to provide information by describing one by one the equipment used in the implementation of the maguti tradition and describing the construction of the mindset of the Ngawi people towards the maguti tradition. This research method is descriptive qualitative. The source of data is from interviews. The result of this research is that Ngawi people have a mindset that the implementation of this maguti tradition has the aim of “Kangge bucal sengkolone kari segerwarase”, meaning to get rid of all negative things, stay safe. The implementation can be done when the baby is two hundred and forty-five days old, can also be done when stepping into adulthood or before marriage. The equipment (ubo rampe) in the maguti tradition is bucu, jenang abang putih, jenang sepuh, banyu suci, setaman flowers, sego udhuk, sego golong, gedhang setangkep, asahan, kopat lepet.